17. Oxytetracycline Activities To Staphylococcus aureus Biofilm Inhibition Of Aceh Cattle Preputium Isolate - Maryulia Dewi; Darmawi Darmawi; T. Zahrial Helmi; Erina Erina; Basri Gani; Eliawardani Eliawardani; Azhar Azhar (Jurnal Medika Veterinaria, 2019)
The aim of this study was to see the antimicrobial activities of oxytetracycline to the inhibition of Staphylococcus aureus biofilm of Aceh’s cattle preputium isolates. The parameters measured in this study were the percentage of antimicrobial and biofilm inhibitory power. The antimicrobial activities were tested on Nutrient Broth using U-bottom polystyrene microplate 96 wells. The Biofilm stained using 1% of crystalviolet. Then, Optical Density (OD) read at λ 595 nm. The results showed that the oxytetracycline of 10%, 20% and 30% (μg / μL) had the antimicrobial abilities of 28.60% ± 13.23%; 36.30% ± 5.37%; and 57.70% ± 2.23%. In addition, The biofilm inhibitory capacity of oxytetracycline 10%, 20% and 30% (μg / μL) were 2.20% ± 8.77%; 2.70% ± 4.17%; and 3.73% ± 14.14%. Therefore, it can be concluded that the oxytetracycline  had the ability to inhibit the biofilm of Staphylococcus aureus.